Teachers’ Views on Preparation for Employment of Young Autistic People - Biranavan Thavapalan; Anna Remington; Liam Alexander MacKenzie Myles; Emanuele Maria Merlo (Journal of Mind and Medical Sciences)
Background. Contemporary literature indicates that there is significant support and assistance provided by schools for young autistic people, which has had a positive impact on the accessibility of jobs. Nevertheless, the employment rate of autistic people is unacceptably low in the UK. The current study investigated teachers’ views on the preparation for employment of young autistic people in the UK. Methods. Interviews were conducted with individuals from the educational field and thematic analysis was used to explore the teachers’ views regarding the factors that have an impact on the preparation for employment of young autistic people. Results. Four main themes emerged from the analysis. These themes included awareness, funding and government support, action plans and motivation. Conclusion. These results have critical implications for the educational field and future research, which are discussed in the paper.